Respuesta :

Answer: Approximately 0.78388 seconds

==========================================

Explanation:

Plug in t = 0 to find that

h = -16t^2 - 64t + 60

h = -16(0)^2 - 64(0) + 60

h = 60

The starting height is 60 feet.

-----

Now plug in h = 0 and solve for t.

h = -16t^2 - 64t + 60

0 = -16t^2 - 64t + 60

-16t^2 - 64t + 60 = 0

From here use the quadratic formula

[tex]t = \frac{-b\pm\sqrt{b^2-4ac}}{2a}\\\\t = \frac{-(-64)\pm\sqrt{(-64)^2-4(-16)(60)}}{2(-16)}\\\\t = \frac{64\pm\sqrt{7936}}{-32}\\\\t = \frac{64+\sqrt{7936}}{-32} \ \text{ or } \ t = \frac{64-\sqrt{7936}}{-32}\\\\t \approx -4.78388 \ \text{ or } \ t \approx 0.78388 \\\\[/tex]

We ignore the negative t value as a negative time doesn't make sense.

The only practical answer is roughly t = 0.78388 seconds.